2020
DOI: 10.3390/ijerph17217748
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Centered Approach to Nursing Ethics Education: A Qualitative Study

Abstract: Nurses deal with ethical decisions as they protect patients’ rights, but a consensus on effective approaches to nursing ethics education is lacking. The “four topics” method can facilitate decision-making when nurses experience ethical dilemmas in practice. This study aimed to describe nursing students’ perspectives on and experiences of a case-centered approach to nursing ethics education using the four topics method. This qualitative study consisted of two phases. First, we delivered case-centered nursing et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…Understanding one’s own values and attitudes can be facilitated through, for example, role-play or simulation activities [ 54 56 ], narratives [ 40 , 57 , 58 ], storytelling [ 42 ] and discussions in small groups [ 38 , 43 45 , 47 , 59 62 ]. Small group discussions are appropriate when healthcare professionals or students are unwilling to stand out by asking questions or giving individual opinions in learning situations in which many people participate [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding one’s own values and attitudes can be facilitated through, for example, role-play or simulation activities [ 54 56 ], narratives [ 40 , 57 , 58 ], storytelling [ 42 ] and discussions in small groups [ 38 , 43 45 , 47 , 59 62 ]. Small group discussions are appropriate when healthcare professionals or students are unwilling to stand out by asking questions or giving individual opinions in learning situations in which many people participate [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…This programme was beneficial to FDs who were able to develop their own teaching and ethical reasoning skills and to reflect on the influence of the hidden curriculum on their own behaviour Very poor Kuhn et al [ 69 ], Germany Quantitative To improve moral judgment, ethical reflection and strengthen individual resilience in value conflicts 13 medical students and young physicians Web-based evaluation sheet Descriptive statistics Didactic concept with case conferences, discussion about ethics issues and lectures were considered helpful for dealing with ethical questions at the clinic. The format was also relevant for their later profession Fair Langlois et al [ 61 ], Canada Qualitative To explore the experiences and learning of student health professionals engaged in an ethics module 91 health mentor programme students Interviews Thematic analysis Five major themes emerged: (1) patient autonomy and expertise in care, (2) ethical complexity and its inevitable reality in the clinical practice setting, (3) patient advocacy as an essential component of day‑to‑day practice, (4) qualities of remarkable clinicians that informed personal ideals for future practice, and (5) patients’ perspectives on clinician error and how they enabled suggestions for improving future practice Good Lee et al [ 63 ], Korea Qualitative To describe nursing students’ perspectives on and experiences of a case-centred approach to nursing ethics education using the four topics method 10 nursing students Focus group discussion Content analysis Four themes emerged: 1) the importance of ethics education as perceived by nursing students,2) problems in current nursing ethics education, 3) the experience of case-centred nursing ethics education using the four topics approach, and 4) suggestions for improving nursing ethics education Good Lee et al [ 73 ], Korea Quantitative To identify the effects of a nursing ethics seminar on the moral sensitivity and ethical behaviour of nurses working in a hospital setting 35 nurses Questionnaires Analytical and descriptive statistics …”
Section: Methodsmentioning
confidence: 99%
“…Learning focused on group discussions and ethical simulation can also improve students' comprehension of applying nursing ethical principles in clinical contexts (Nash & Harvey, 2017). Recent research also explains that learning methods using a case-centered approach and connecting theory with clinical practice can increase nursing students' ethical knowledge (Lee et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In In the program of empowering nurses in this study, real ethical cases and issues were used by group discussion with the participation of nurses. In this regard, the study results of Lee et al (29) showed that students prefer nursing ethics focused on providing opportunities for learning ethical issues in the clinical setting and solving ethical problems, and nursing educators should systematically provide opportunities for nursing students to discuss real situations and allow them to solve ethical problems practically. This study emphasized that without teaching nursing ethics, nursing students do not even recognize ethical issues in the clinical setting, let alone having basic knowledge to judge ethical issues.…”
Section: Methodsmentioning
confidence: 99%